Diagnostic value of exercise stress echocardiography on a horizontal cycle ergometer in patients with low-risk non-ST elevation acute coronary syndrome - E. E. Abramenko; T. R. Ryabova; I. I. Yolgin; V. V. Ryabov (Российский кардиологический журнал, 2023)
Aim. To evaluate the diagnostic accuracy of exercise stress echocardiography on a horizontal cycle ergometer for the detection of obstructive coronary artery disease (CAD) in patients with low-risk non-ST-elevation acute coronary syndrome (NSTE-ACS).Material and methods. The study included 95 patients aged 53 (46;63) years (men, 58%), hospitalized in the regional vascular center with low-risk NSTE-ACS. Patients with known CAD, impaired resting left ventricular contractility were not included. During hospitalization, standard stress echocardiography on a horizontal cycle ergometer and invasive or non-invasive coronary angiography (CAG) were performed. All values of coronary obstruction ≥70% were verified by invasive CAG. The assessment of myocardial revascularization was observational.Results. All patients had normal structural and functional cardiac parameters at rest. No adverse events were recorded during the tests. The result of stress echocardiography according to impaired local contractility (ILC) criterion was positive in 9 (16%), negative in 28 (49%), incomplete symptom-limited in 20 (35%) patients. Coronary artery stenosis ≥50%/≥70% was detected in 78/78% of cases in the subgroup with a positive result, in 29/11% — with a negative result, 30/10% — with a non-diagnostic result. The association of ILC with stenosis ≥70% was higher, with an odds ratio of 30,1 (4,9; 186,5) vs 8,5 (1,6; 46,1) for stenosis ≥50%. There were following diagnostic accuracy for stenosis ≥70%: sensitivity — 70%, specificity — 93%, positive predictive value — 78%, negative predictive value — 89%, overall accuracy — 86%.Conclusion. Exercise stress echocardiography on a horizontal cycle ergometer in patients with low-risk NSTE-ACS patients is safe and feasible. The method has moderate sensitivity and positive predictive value and high specificity, negative predictive value and overall accuracy for the detection of anatomically significant coronary artery stenosis. In the structure of results, there is a significant proportion (35%) of symptom-limited tests incomplete due to heart rate, characterized by the lowest incidence of obstructive atherosclerosis.